Schooling the national imagination : education, English, and the Indian modern - Advani, Shalini (New Delhi ; Oxford : Oxford University Press, 2009)
'Schooling the National Imagination' examines English Studies in the school curriculum in India and, using this as a lens, also explores the shifts in the construction of nationalism modernity, and identity in independent India.
Includes bibliographical references and index.
Description based on print version record.
Keywords: English language -- Study and teaching -- India; Education and state -- India